Assessment of the internal construct validity of the revised High-Level Mobility Assessment Tool for traumatic orthopaedic injuries. (May 2014) - Hill, Bridget; Kahn, Michelle; Pallant, Julie; Williams, Gavin
Objective: To determine whether the revised High-Level Mobility Assessment Tool (HiMAT) was valid for measuring mobility for people with multi-trauma orthopaedic lower limb injuries. Design: Cross-sectional study. Subjects: Participants with lower limb multi-trauma orthopaedic injuries. Methods: One complete revised HiMAT was obtained for 106 people within 12 weeks of being allowed to fully weight bear. Rasch analysis was used to assess the overall fit of the model for individuals and items, differential item functioning, local dependency, targeting of items and dimensionality. Results: The mean revised HiMAT score was 10.5 (SD = 6.8) with a range of 5–30. Rasch analysis of revised HiMAT showed adequate overall fit to the model ( P = 0.29) with no misfitting items (fit residual SD = 0.69) or persons (fit residual SD = 0.62). The scale showed good internal consistency (Person Separation Index = 0.91). One item (hopping) demonstrated disordered thresholds, however this item had good fit to the model in all other aspects. The revised HiMAT was unidimensional, and no differential item functioning was detected for gender or age. The revised HiMAT was well targeted for this group with a range of items across all ability levels. Conclusion: The results of this study support the internal construct validity of the revised HiMAT as a well-targeted, unidimensional measure of high-level mobility with no ceiling or floor effect for males and females recovering from multi-trauma orthopaedic lower limb injuries.